3D printing of CaO-based ceramic core using nanozirconia suspension as a binder. Issue 15 (December 2017) - Zhao, Huoping; Ye, Chunsheng; Fan, Zitian; Wang, Changming
Abstract: The 3D printing of a ceramic core with nanoceramic suspension as a binder was performed to investigate a novel method for the fabrication of a complex-shaped ceramic core. Green bodies were printed using CaO powder as a precursor material and nanozirconia-absolute ethyl alcohol solution suspension as a binder. The green bodies were sintered at 1300–1500 °C for 2 h. The effects of binder saturation level on the properties of the sintered bodies were investigated. Increasing the binder saturation level caused decreases in the linear shrinkage of the sintered bodies, but increases in hydration resistance and bending strength. The nanozirconia particles were deposited on the surfaces of the CaO particles and filled the pores of green bodies, and then formed a high melting temperature CaZrO3 layer with the CaO at the surfaces of the CaO grains, which improved the hydration resistance of the CaO-based ceramic core parts.